P. J. VAN DER VOORT: The Pen and the Quarter-Deck. A study of the Life and Works of Capt Frederick Chaumier, R.N. - Ploeger, Jan (Scientia Militaria - South African Journal of Military Studies, 2012)
Narratives with a military historical theme, which run their courses at sea, have an especial fascination for a large number of readers. Presumably the inherent reason for this stems from a longing for adventure and the element of suspense which distinguishes works of this nature.